Macroeconomic surprises, market environment, and safe-haven currencies - Adrian Jäggi; Martin Schlegel; Attilio Zanetti (Swiss Journal of Economics and Statistics, 2019)
We study the reaction of the CHF and JPY to macroeconomic surprises and changes in the broader market environment before and during the crisis using high-frequency data. Results show that the CHF and JPY are traditionally more sensitive to macroeconomic surprises than other currencies, reflecting the fact that macroeconomic surprises impact uncertainty and risk aversion. This link was further magnified during the crisis and could not be broken by the specific measures adopted by monetary authorities to limit the appreciation trend. We also find some evidence that, during the crisis, CHF and JPY responded more strongly to surprises generating an appreciation than to surprises leading to a depreciation. Additionally, both currencies also systematically respond to changes in the general market environment. This result is robust to the use of two measures of the market environment: VIX and on a novel index based on Bloomberg wires.
Keywords: F31; G12; G14; 330; Safe-haven currencies; Swiss franc; Yen; Macroeconomic surprises; Risk